2018
DOI: 10.1038/s41598-018-35706-8
|View full text |Cite
|
Sign up to set email alerts
|

The characteristic, antioxidative and multiple organ protective of acidic-extractable mycelium polysaccharides by Pleurotus eryngii var. tuoliensis on high-fat emulsion induced-hypertriglyceridemic mice

Abstract: The antioxidant and multiple organ protection effects of acid- extracted mycelia polysaccharides (Ac-MPS) from Pleurotus eryngii var. tuoliensis on HFE-induced hypertriglyceridemic mice were investigated. The results showed that Ac-MPS have potential ability to relieve the hypertriglyceridemia and preventing oxidative stress by decreasing levels of TG, TC LDL-C, elevating contents of HDL-C in serum, increasing the activities of SOD, GSH-Px, CAT and T-AOC, and the down regulating MDA and LPO contents in liver, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…The antioxidant enzymes include CAT, POD, and SOD, which play important roles in mitigating oxidative damage (Halo et al, 2015; Parviz et al, 2015). SOD catalyzes the transformation of accumulated ROS into H 2 O 2 and molecular oxygen species, whereas CAT and POD convert H 2 O 2 into water and molecular oxygen for the elimination of ROS (Gao et al, 2018; Ragupathy et al, 2016; Sousa et al, 2020). In addition, the variation in SOD activity (Figure 4a) in AM plants was lower than that in POD (Figure 4c) and CAT (Figure 4b) activities at the inoculum sizes of 40 and 60 g, potentially because POD and CAT had a higher capacity for the decomposition of H 2 O 2 generated by SOD (Cai & Gao, 2020) or because SOD, CAT, and POD had different sensitivities to different strains and inoculum sizes (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant enzymes include CAT, POD, and SOD, which play important roles in mitigating oxidative damage (Halo et al, 2015; Parviz et al, 2015). SOD catalyzes the transformation of accumulated ROS into H 2 O 2 and molecular oxygen species, whereas CAT and POD convert H 2 O 2 into water and molecular oxygen for the elimination of ROS (Gao et al, 2018; Ragupathy et al, 2016; Sousa et al, 2020). In addition, the variation in SOD activity (Figure 4a) in AM plants was lower than that in POD (Figure 4c) and CAT (Figure 4b) activities at the inoculum sizes of 40 and 60 g, potentially because POD and CAT had a higher capacity for the decomposition of H 2 O 2 generated by SOD (Cai & Gao, 2020) or because SOD, CAT, and POD had different sensitivities to different strains and inoculum sizes (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…tuoliensis , is a large edible fungus with a high economic value in China as well as a pleasant taste, delicious flavor and health benefits 1 . The polysaccharide content in the fruiting body is about 19.0%, with pharmaceutical functions, including enhancing immunity and antioxidative, 2 antitumor 3 and cardioprotective effects 4 . Because of its delicious taste and medicinal values, P. tuoliensis has become prevalent in Eastern Asian countries, such as China, Japan and Korea.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SOD and GSH-Px are antioxidant enzymes that respond to the strength of antioxidant capacity. 33 SOD acts as an intracellular oxygen radical scavenger, catalyzing the conversion of O 2 − to O 2 and H 2 O 2 , thereby protecting the organism from superoxide anions. 34 GSH-Px is an important peroxide-degrading enzyme that is widely present in the body.…”
Section: Discussionmentioning
confidence: 99%